2013
DOI: 10.3916/c41-2013-03
|View full text |Cite
|
Sign up to set email alerts
|

Internationalization and coauthorship in major communication journals in Spain

Abstract: La internacionalización y las coautorías en las principales revistas científicas de Comunicación en España❖ Eudald Escribà-Sales is PhD Student of the Department of Communication at the Universitat Pompeu Fabra in Barcelona (Spain) (eudald.escriba01@estudiant.upf.edu). ❖ Dr. Sergi Cortiñas-Rovira is Senior Lecturer of the Department of Communication at the Universitat Pompeu Fabra in Barcelona (Spain) (sergi.cortinas@upf.edu). ABSTRACTThis work has conducted an analysis of Spanish Communication journals in ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 7 publications
2
3
0
4
Order By: Relevance
“…The regional analysis also shows that research on land use and related policy and socio‐economic studies tend to be associated to international comparisons and are produced by the two regions (Centre‐ Madrid, North Mediterranean‐ Barcelona) that concentrate the largest number of research institutions and universities. This is consistent with the findings of general Spanish bibliometric studies (Escribà & Cortiñas, ), pointing to a possible size effect threshold that facilitates multidisciplinarity.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The regional analysis also shows that research on land use and related policy and socio‐economic studies tend to be associated to international comparisons and are produced by the two regions (Centre‐ Madrid, North Mediterranean‐ Barcelona) that concentrate the largest number of research institutions and universities. This is consistent with the findings of general Spanish bibliometric studies (Escribà & Cortiñas, ), pointing to a possible size effect threshold that facilitates multidisciplinarity.…”
Section: Resultssupporting
confidence: 91%
“…We searched for publications in Web of Science (WoS), both from the Science Citation Index and Social Science Index. Spanish research published in international refereed journals started in the late 1980s (Jiménez-Contreras et al, 2003;Escribà & Cortiñas, 2013;Purnell & Quevedo-Blasco, 2013). As we wanted to assess the impact of the UNCCD, we selected four sexennial periods, one prior to the signing of the Convention and the following three.…”
Section: Data Collectionmentioning
confidence: 99%
“…The authors conclude that the use of these algorithms makes it possible to describe the retrospective evolution of the research groups, break them down into sub-groups with their own personality (in the case of macro-groups), identify research topics (in addition to publications and quotations received), identify which ones are collaborations by the group with other research centres, and even propose a leader, who is not necessarily the author of all the group's publications. Several studies on co-authorship in communication have been identified, focusing on a journal (López-Ornelas, 2010), on a specific database like Scopus (Costa-Sánchez, 2017) or on a selection of journals in the field (Fernández-Quijada, 2011; Escribá & Cortiñas, 2013).…”
Section: Establishment Duration Leadership Strategy and Efficiencymentioning
confidence: 99%
“…Junto al incremento de la producción científica en forma de artículos en revistas especializadas, otro de los indicadores del impacto que pudiera estar teniendo este nuevo contexto institucional en las prácticas de la comunidad académica es el relativo a lo que proponemos denominar régimen de autoría de la investigación publicada, entendiendo por tal modalidades como la autoría individual o colaborativa (co-autorías) de los textos publicados. Esta cuestión ha comenzado a atenderse también recientemente (Castillo y Carretón, 2010;Castillo, Rubio y Almansa, 2012;Fernández Quijada, 2010y 2011Fernández Quijada y Masip, 2013;Fernández Quijada, Masip y Bergillos, 2013;Escribà y Cortiñas, 2013;Masip, 2011;Roca y Pueyo, 2012), con resultados que permiten trazar la evolución del régimen de autoría de la investigación española sobre comunicación en los últimos años.…”
Section: Introductionunclassified